High public debt in an uncertain world: Post-Covid-19 dangers for public finance - Daniel Gros (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
In this EconPol Policy Brief Daniel Gros cautions countries with high debt ratios not to simply rely on low interest rates to make their (Covid-19) debt sustainable. Now that the health emergency is subsiding, governments have to chart a new course for public finance. The starting point is a higher level of public debt. However, high debt ratios represent a danger, even when interest rates are low. The key reason is increased uncertainty of growth prospects in a post-Covid-19 economy, coupled with an uncertainty regarding the probability of future large shocks. A prudent policy would therefore be to start reducing debt levels to pre-crisis levels as soon as the economy normalizes, according to the author. Key messages: High debt ratios represent a danger, even if interest rates are low. - The key reason is increased uncertainty of growth prospects in a post-Covid economy coupled with and uncertainty with regard to the probability of future large shocks. - Large negative shocks are more frequent than assumed in standard models. - Another reason is that the cost of public debt might increase more than linearly as the debt ratio rises. - Large negative shocks create much more problems when debt is already high.
Keywords: 330; Öffentliche Schulden; Coronavirus; Welt